Intimate partner violence among women of reproductive age during the COVID-19 pandemic in Ethiopia: a systematic review and meta-analysis - Gizachew Yilak; Alemayehu Sayih Belay; Aychew Kassie; Befkad Derese Tilahun; Ambaw Abebaw Emrie; Mulat Ayele; Eyob Shitie Lake; Legese Fekede Abza (BMJ Public Health)
Objectives Intimate partner violence (IPV) is the violence committed by both current and former spouses and partners, and the rate of this violence is known to increase during different pandemics. The pooled prevalence of IPV among pregnant women before the COVID-19 pandemic was 37%, however, the pooled prevalence of IPV among women during COVID-19 is not yet known. Therefore, this study aimed to assess the pooled prevalence of IPV and its determinants among women of reproductive age during the COVID-19 pandemic in Ethiopia.Design Systematic review and meta-analysis.Data sources The review was done as per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline using different search databases such as: PubMed/Medline, Cochrane Library, Virtual Health Library Regional Portal, HINARI (research4life), and Google Scholar.Eligibility criteria Those quantitative studies conducted in Ethiopia during the COVID-19 pandemic, that reported the prevalence of IPV among women of reproductive age, and were published in English from 13 March 2020 to 15 October 2025, were included for this study.Data extraction and synthesis All authors independently extracted data using the Joanna Briggs Institute manual for evidence synthesis. Any incongruity of the result in the data extraction process was resolved through discussions and consensus (ie, a Delphi process). The data were analysed using Stata Corp V.11 software. The heterogeneity between studies was assessed using I2 test statistics and the random-effects meta-analysis was done using the restricted maximum likelihood method. Publication bias was assessed using funnel plots, and Egger’s and Begg’s tests.Result In this study, a total of 802 articles were identified using different electronic databases. Finally, 12 studies that fulfilled the eligibility criteria were included for systematic review and meta-analysis. A total of 7397 study participants were sampled from April 2020 to August 2021. The overall estimated pooled prevalence of IPV was 33.5% (95% CI 22.9% to 44.1%) and the prevalence of physical, psychological and sexual violence was 16.4%, 28.2% and 17.4%, respectively. Different factors such as: age of the young women (adjusted odds ratio (AOR)=3.24; 95% CI 0.6, 5.8, p=0.015), lack of formal education (AOR=2.63; 95% CI 1.7, 3.6, p=0.000), partner’s substance use (AOR=2.07; 95% CI 1.5, 2.7, p=0.000), partner not attending formal education (AOR=3.38; 95% CI 2.2, 4.6, p=0.000) and partner’s alcohol use (AOR=2.82; 95% CI 1.1, 4.6, p=0.000) were found to be significantly associated with IPV among women during the COVID-19 pandemic.Conclusions In this study, a third of women of reproductive age experienced IPV during the COVID-19 pandemic. Women whose partners used alcohol and other substances were found to be vulnerable to IPV. Therefore, this finding gives an insight for policymakers to focus on empowering women and their partner’s economic and educational status, promoting health education for partners towards the negative impact of bad behaviours like alcohol and other substance utilisation on their health, and the physical, mental and social wellbeing of women. Moreover, the burden of IPV is increased not only during such a pandemic but also during different internal displacements, conflicts and unrest. Therefore, we recommend policymakers to frequently assess IPV-related burdens during such events and act accordingly.